hx = f(x) - g(x)
f(x) = -2x + 17
g(x) = -5x - 10
You can substitute/plug in (-2x + 17) into "f(x)" since f(x) = -2x + 17, and you can substitute (-5x - 10) into "g(x)" since g(x) = -5x - 10.
h(x) = f(x) - g(x)
h(x) = (-2x + 17) - (-5x - 10) Now simplify, first distribute -1 into (-5x - 10)
h(x) = (-2x + 17) - (-1)5x - (-1)10 (two negative signs cancel each other out and become positive)
h(x) = -2x + 17 + 5x + 10 Combine like terms (terms that have the same variable and power/exponent)
h(x) = 3x + 27